The Impact of Employer Branding Towards Intention to Apply on Novo Club Community Batch 1 with Corporate Reputation as Mediation Variable - Shofia Mumtaz Alifa; Vita Sarasi (Syntax Corporation Indonesia, 2023)
This study aims to examine the effect of employer branding on the intention to apply by mediating variable corporate reputation in Novo Club Community Members Batch 1. The data in this study were tested using the SEM-PLS (Structural Equation Modeling-Partial Least Square) method by sampling using purposive sampling techniques to 157 respondents who were active members of Novo Club Batch 1. The data in this study was obtained through questionnaires that were distributed using the help of google forms and processed using SmartPLS 3.0 software. The result of this study is that employer branding through corporate reputation has no positive and significant effect on the intention to apply with T-statistical values of 1,485<1.96 and P-values of 0.138>0.05. Therefore, ParagonCorp needs to carry out a new strategy that is more targeted and measurable to improve the company's good reputation.